Sensing the sacred: A small group worship experience for those with Alzheimer's and other dementias: A conference presentation from the 6th International Conference on Spirituality and Aging - Gordon, Nancy (Journal of religion, spirituality & aging, 2018)
Sensing the Sacred, a worship program designed for small groups of persons with Alzheimer's disease or other dementias, is beneficial for long term care residences and for congregations in ministry to their congregants and neighbors. It was developed from the work of Sonja Stewart, co-developer of the Young Children and Worship program, which uses wooden figures to tell Biblical stories and builds on the techniques of Maria Montessori. The paper describes development of this program and offers counsel on how to use it.